2015
DOI: 10.4238/2015.may.29.11
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rhizoma paridis total saponins on apoptosis of colorectal cancer cells and imbalance of the JAK/STAT3 molecular pathway induced by IL-6 suppression

et al.

Abstract: ABSTRACT. We observed the influence of different concentrations of Rhizoma paridis total saponins (RPTS) on the apoptosis of colorectal cancer cells and explored the internal mechanism involved. We determined whether RPTS influences the interleukin-6 (IL-6)/Janus kinase (JAK)-signal transducer and activator of transcription-3 (STAT3) apoptosis molecular pathway and looked for colon cancer-related signal transduction pathways or targets inducing apoptosis. We also cultured SW480 colorectal cancer cells using di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…et al, 2022 ), Paris saponin H (induces cell apoptosis, suppresses EMT and invasion in liver cancer cells) ( Chen et al, 2019 ), formosanin C (inhibits pulmonary metastasis on mouse lung adenocarcinoma) ( Man et al, 2011b ), and gracillin (induces apoptosis and inhibits migration in BGC823 cells) ( Liu et al, 2021 ). In additional, previous studies have demonstrated anticancer activities of polyphyllin in Rhizoma Paridis in a variety of cancers, including lung cancer ( Shuli et al, 2011 ), gastric cancer ( Sun et al, 2007 ), colon cancer ( Teng et al, 2015 ), prostate cancer ( Zhang et al, 2018 ), and melanoma ( Man et al, 2011a ). Although increasingly more scientists and experts in the medical field have researched the active ingredients in Rhizoma Paridis, due to its complex combination of active ingredients and anticancer mechanisms ( Zhang et al, 2010 ), further research is needed to reveal the mechanism of some active ingredients in Rhizoma Paridis.…”
Section: Research Backgroundmentioning
confidence: 99%
“…et al, 2022 ), Paris saponin H (induces cell apoptosis, suppresses EMT and invasion in liver cancer cells) ( Chen et al, 2019 ), formosanin C (inhibits pulmonary metastasis on mouse lung adenocarcinoma) ( Man et al, 2011b ), and gracillin (induces apoptosis and inhibits migration in BGC823 cells) ( Liu et al, 2021 ). In additional, previous studies have demonstrated anticancer activities of polyphyllin in Rhizoma Paridis in a variety of cancers, including lung cancer ( Shuli et al, 2011 ), gastric cancer ( Sun et al, 2007 ), colon cancer ( Teng et al, 2015 ), prostate cancer ( Zhang et al, 2018 ), and melanoma ( Man et al, 2011a ). Although increasingly more scientists and experts in the medical field have researched the active ingredients in Rhizoma Paridis, due to its complex combination of active ingredients and anticancer mechanisms ( Zhang et al, 2010 ), further research is needed to reveal the mechanism of some active ingredients in Rhizoma Paridis.…”
Section: Research Backgroundmentioning
confidence: 99%
“…In recent years, the antitumor research of steroidal saponin extract from P. polyphylla var. yunnanensis has become hot, which can inhibit the growth of malignant tumors, such as lung cancer, colon cancer, liver cancer, bladder cancer, and so on [4][5][6][7]. Polyphyllin II was found to promote Ros-mediated apoptosis of Bax/Cyt-c cells, leading to the inhibition of glioma cell growth and invasion [8].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the antitumor pharmacological activity of Rhizoma Paridis extracts has emerged a major focus of research. Recent several years, polyphylla saponins have been widely reported to inhibit tumor growth in cancer of the breast [13], liver [14], lung [15], ovary [16], and colon [17], as well as other types of malignancy. All these findings bring lights to the discovery of new drugs for cancer.…”
Section: Introductionmentioning
confidence: 99%